An investigation on the cost implications of methodology of sub-contract work pricing - Dow, Ian; Sertyesilisik, Begum; Ross, Andrew (EMERALD GROUP PUBLISHING LTD, 2009)
Purpose - The purpose of this paper is to identify how much particular variables influence the cost differences between order values and final accounts for certain trade subcontractors. Design/methodology/approach - The methodology consists of a literature survey and a case study. A sample of 33 projects, undertaken by a contracting organisation, are analysed as a basis for testing their significance. Findings - For highly asset specific transactions the research suggests that the level of variables which can affect their performance is greatest, suggesting integration within the contracting firm to mitigate the threat of opportunistic behaviour. Procurement route utilised on a project was strongly linked to outturn cost performance, as is inclusion in the tender bid, suggesting earlier subcontractor involvement through design and build and partnering arrangements is significantly better at managing subcontractor cost performance than traditional routes. Originality/value - The market volatility of the construction industry has meant the procurement of subcontractors has long been established as an important part of the project coalition. Transaction cost economic theory has recently become popular within the construction research industry. Much of this research has examined the vertical boundaries to which a construction firm is subjected when considering integration of trades or continued use of subcontractors. Empirical data on the cost performance of subcontractors within a project environment are not widely available. For this reason, this research aids practitioners and researchers by identifying why particular variables influence the cost differences between order values and final accounts for certain trade subcontractors.
Keywords: Transaction costs; Procurement; Subcontracting; Construction industry; Business & Economics